2011
DOI: 10.1021/ie1016305
|View full text |Cite
|
Sign up to set email alerts
|

Admicellar Polymerization and Mixing in a Laboratory Dyeing Unit-A Variant of Rocking Reactors

Abstract: Mass transfer in a laboratory dyeing machine, consisting of cylindrical canisters mounted on a carousel with a horizontal axis, has been examined to adapt the unit for modification of cotton by admicellar polymerization. Canisters located at the periphery of the carousel are canted relative to the axis of rotation so that fluid in the canister moves front-to-back and back-to-front over the course of one revolution in a fashion similar to a rocking reactor. Dissolution of benzoic acid in water at 30 °C has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…(Table XIII is a compilation of the polymerization process parameters of all the applications of ADPM cited in this review.) There has been a study to perform ADPM in laboratory dyeing units, 122 and its industrial developments for inorganic substrates have been reported. 123 Substantial literature [124][125][126][127][128][129][130][131][132][133][134] is also available on ADPM, which highlights its potential in commercial application.…”
Section: Resultsmentioning
confidence: 99%
“…(Table XIII is a compilation of the polymerization process parameters of all the applications of ADPM cited in this review.) There has been a study to perform ADPM in laboratory dyeing units, 122 and its industrial developments for inorganic substrates have been reported. 123 Substantial literature [124][125][126][127][128][129][130][131][132][133][134] is also available on ADPM, which highlights its potential in commercial application.…”
Section: Resultsmentioning
confidence: 99%